AvaliaÃÃo da PolÃtica de HabitaÃÃo no MunicÃpio de Fortaleza: O Caso da Demanda EspontÃnea na InstituiÃÃo Executora Local. - Duane Brasil Costa (2013)
The research deals with the urban issue, focusing on the housing issue as a product of concentration of capital and the exploitation of the workforce, and aims to analyze the configuration of spontaneous demand in housing policy implemented by the Housing Development Foundation Fortaleza (Habitafor). To achieve the proposed objective methodology was used to conduct a literature and documents on legal contributions that support the housing policy in Fortaleza and how it was established, in addition to conducting interviews with professionals working in the institution in meeting spontaneous demand. The research findings show that practitioners who perform policy in the municipality has no knowledge of when, how and why the spontaneous demand was created by the institution and show that did not believe in the same. We understand that the housing shortage is not reported as an isolated fact, but as fact induced by urbanization and how urban space is planned to serve the logic of capital in its historical moment. It is possible to conclude that spontaneous demand serves as a containment strategy claim by individuals seeking Habitafor to request a housing unit.